Blasting Results Compared Using Crusher Powder Consumption and Tonnage of Rock Produced - Ron Glowe (International Society of Explosives Engineers, 2005)
This paper shows the potential of a new computer model, using the Glowe-Tech (GT) Tonnage Analyzer program to compare drilling and blasting results. This model uses the crushers and conveyors as measuring tools in aggregate quarries in the USA and Canada. All data is collected using commercially available kilowatt transducers and an analog input/output automation module. There are two areas of measurement used to compare results. The first area is the tonnage moved by key conveyors to show the split in products produced and the actual rate of production. If belt scale readings are not available then the Glowe-Tech Tonnage Analyzer can be used to convert kilowatts from the conveyor motor to tonnage. The second is the tons of rock crushed per kilowatt hour of energy consumption by the primary and secondary (optional) crushers. This modeling process works best if blasts are mucked and crushed in sequence. There are many other variables such as crusher types, crusher settings, screen sizing and actual geology in the pit that can influence the results, however if variables can be standardized then definite trends can be seen when comparing drilling and blasting results